Immersive VR safety training: Enhancing hazard recognition and compliance through 5M and 5S integration - Abdallah Al-Hamad; Attila Gilányi (Results in Engineering)
Advancing a new frontier in workplace safety and forging a new boundary in accident prevention, this study redefines safety training by harnessing immersive Virtual Reality (VR) to integrate the 5M framework (Material, Machine, Man, Method, Measurement), a sharp tool for pinpointing workplace accident root causes, with the 5S approach (Sort, Set in Order, Shine, Standardize, Sustain), a dynamic strategy for masterful risk mitigation, addressing the persistent challenges of inconsistent application and fading engagement in traditional practices. Through meticulous industrial site observations and reviewing accident records, it expose prevalent hazards. It dissects faltering safety systems, while qualitative insights from 20 safety experts illuminate current methods, unveiling VR's potential to revolutionize adherence to gold standard protocols. Employing the Analytic Hierarchy Process (AHP) with 10 expert inputs, training options are ranked across five critical criteria: hazard recognition, safety compliance, realism, integration, and knowledge retention. Results reveal VR as the top countermeasure at 45%, outpacing computer-based training at 29% and traditional methods at 26%, transforming 5S and 5M principles into vivid simulations that sharpen risk detection, enhance workplace organization, and solidify procedural mastery. Experts praise VR's ability to spark engagement, heighten situational awareness, and embed safety protocols, particularly in high-risk industrial arenas, offering a bold blueprint for VR programs that boost efficiency and safeguard lives in a thrilling leap forward for accident prevention.